The Peculiar Radio Evolution of the Tidal Disruption Event ASASSN-19bt - Christy, C.T.; Alexander, K.D.; Margutti, R.; Wieringa, M.; Cendes, Y.; Chornock, R.; Laskar, T.; Berger, E.; Bietenholz, M.; Coppejans, D.L.; De Colle, F.; Eftekhari, T.; et al. (2024)
We present detailed radio observations of the tidal disruption event (TDE) ASASSN-19bt/AT 2019ahk, obtained with the Australia Telescope Compact Array, the Atacama Large Millimeter/submillimeter Array, and the MeerKAT radio telescopes, spanning 40-1464 days after the onset of the optical flare. We find that ASASSN-19bt displays unusual radio evolution compared to other TDEs, as the peak brightness of its radio emission increases rapidly until 457 days post-optical discovery and then plateaus. Using a generalized approach to standard equipartition techniques, we estimate the energy and corresponding physical parameters for two possible emission geometries: a nonrelativistic spherical outflow and a relativistic outflow observed from a range of viewing angles. We find that the nonrelativistic solution implies a continuous energy rise in the outflow from E ∼ 1046 to E ∼ 1049 erg with outflow speed β ≈ 0.05, while the off-axis relativistic jet solution instead suggests E ≈ 1052 erg with Lorentz factor Γ ∼ 10 at late times in the maximally off-axis case. We find that neither model provides a holistic explanation for the origin and evolution of the radio emission, emphasizing the need for more complex models. ASASSN-19bt joins the population of TDEs that display unusual radio emission at late times. Conducting long-term radio observations of these TDEs, especially during the later phases, will be crucial for understanding how these types of radio emission in TDEs are produced.